The Effect of Hydrostatic Initial Stress on the Plane Waves in a Fiber-Reinforced Magneto-Thermoelastic Medium with Fractional Derivative Heat Transfer - Sarkar, N.; Atwa, S.Y.; Othman, M.I.A. (Прикладная механика, 2016)
An effect of three factors - the order of fractional derivative, the hydrostatic initial stress, and parameter of magnetic field – on the plane waves in the half-space made of fiber-reinforced material, that is described by the theory of generalized magnetothermoelasticity, is studied. The problem is solved numerically using the normal mode analysis. The results correspond to the Lord-Shulman model and the model, that uses the fractional derivatives and are presented in the form of graphs. The findings show pronounced effect of mentioned three factors. The results are compared with the case, when the initial stress and magnetic field are absent. Вивчено вплив трьох факторів – порядку дробових похідних, початкового гідростатичного напруження, параметру магнітного поля – на плоскі хвилі в півпросторі з армованого волокнами матеріалу, який описується теорією узагальненої магнітотермопружності. Задача розв’язана чисельно за допомогою аналізу нормальних мод. Результати аналізу відповідають моделі Лорда – Шульмана і моделі, що описується за допомогою дробових похідних, і представлені у вигляді графіків. Отримані результати показують добре виражений вплив вказаних трьох факторів. Також ці результати порівнюються з результатами, що отримані для випадку відсутності початкового гідростатичного напруження і магнітного поля.